2007
DOI: 10.1590/s0104-56872007000300004
|View full text |Cite
|
Sign up to set email alerts
|

Influência de paradigmas temporais em testes de processamento temporal auditivo

Abstract: Temporal variables such stimuli duration and type of task (discrimination and ordering) can interfere in the performance of children in tests of auditory temporal processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
0
4
0
13
Order By: Relevance
“…A avaliação do processamento auditivo é multidimensional, devendo incorporar tanto a análise acústica do sinal quanto os processos cognitivos superiores 13 . Muitas evidências sugerem que as habilidades do processamento temporal são a base do processamento auditivo, especificamente no que concerne à percepção de fala por meio da ordem de eventos, sonoridade de fonemas, discriminação de palavras similares, duração e ordenação das consoantes 1,3,13,15 . devendo portanto ser analisada durante o processo diagnóstico 3,9,16 .…”
Section: Métodounclassified
“…A avaliação do processamento auditivo é multidimensional, devendo incorporar tanto a análise acústica do sinal quanto os processos cognitivos superiores 13 . Muitas evidências sugerem que as habilidades do processamento temporal são a base do processamento auditivo, especificamente no que concerne à percepção de fala por meio da ordem de eventos, sonoridade de fonemas, discriminação de palavras similares, duração e ordenação das consoantes 1,3,13,15 . devendo portanto ser analisada durante o processo diagnóstico 3,9,16 .…”
Section: Métodounclassified
“…como uma das causas das Dificuldades de Aprendizagem da Leitura e da Escrita. Logo, a audiologia tem reconhecido que não somente as alterações condutivas e neurossensoriais determinam distúr-bios de linguagem e aprendizagem, valorizando também o Processamento Auditivo 24 .…”
Section: Tabela 4 -Frequências Das Alterações No Teste Psi Em Ambos Ounclassified
“…A longitudinal study conducted with 236 German children, who were monitored for twenty months, found that auditory temporal order thresholds have a causal influence on literacy development (7) . There is evidence that the temporal aspects are the basis of auditory processing, especially regarding speech perception of sound, duration and ordering of phonemes and identification of words (4,8) , and must therefore be considered for diagnosis (2) . In addition to issues related to auditory temporal processing, socioeconomic characteristics and social risks can exert great influence on the cognitive and language development of children (9) .…”
Section: Introductionmentioning
confidence: 99%